Adaptive ready-to-send and blocking notification (RSBN) scheme in wireless ad hoc networks - Kheong, C.W. (IEEE Computer Society, 2014)
The traditional Request-To-Send/Clear-To-Send (RTS/CTS) handshaking has been widely adopted in wireless ad hoc networks to reduce the hidden terminal problem. Nevertheless, the RTS/CTS handshaking potentially incur the false blocking problem where nodes blindly defer when they overhear the RTS packets. To mitigate the false blocking problem, the Ready-To-Send and Blocking Notification (RSBN) scheme was proposed previously. In the RSBN scheme, the exposed and hidden receivers should transmit the BN packets to inform adjacent nodes of their deferring status to reduce the unnecessary RTS packet transmissions from potential senders. However, implementing the RS and BN control packets in conjunction with the RTS/CTS handshaking can potentially exacerbate the problems of transmission overhead and energy efficiency degradation. In this paper, we propose an improved scheme that is able to switch adaptively between the RSBN scheme and the basic scheme. In some situations where there are only a few hidden terminals with low loads, it is not beneficial to employ the RSBN scheme. Simulation results show that the proposed adaptive scheme can provide significant energy savings with an average reduction of 30 when compared to the default case, where the RSBN scheme is employed at all times. Â© 2014 IEEE.